Racial Differences in Barriers to Blood Pressure Control in a Family Practice Setting - Jonathan M. Scott MS, RD, LD; Colleen K. Spees MEd, RD, LD; Christopher A. Taylor PhD, RD, LD; Randy Wexler MD, MPH, FAAFP (SAGE Publishing, 2010)
Objective: Hypertension prevalence in the African American community is greater than in all other ethnic groups. Cultural perceptions of health and disease introduce barriers to providing effective care. The purpose of this study was to identify racial differences in the perceived causes of hypertension, current behaviors performed to control blood pressure, and perceived barriers to preventing or treating hypertension. Methods: A self-administered survey of patients seen for medical care in a primary care network was conducted. The survey was developed to measure perceptions of hypertension etiology and treatments. Data from African American (n = 69) and Caucasian (n = 218) respondents were used to assess racial differences in perceptions of blood pressure control. Results: About half of respondents knew their current blood pressures. African American patients were significantly less likely to believe that hypertension was caused by a lack of exercise and obesity. Significantly more Caucasians were less likely to report cutting down on table salt and taking prescription medications for blood pressure control. Both African Americans and Caucasians believed that sodium reduction was the most easily changed behavior to control their blood pressure, while both groups identified weight loss as being the most difficult. Conclusion: Racial differences exist in the perceived causes and treatments of high blood pressure, indicating a need for further patient education. When treating and counseling patients, physicians and support staff members must be sensitive to racial diversity and strive to offer culturally relevant solutions, especially for behaviors perceived as most difficult to change.